An acute exercise at low to moderate intensity attenuated postprandial lipemia and insulin responses - Lisa L. Ji; Vicki S. Fretwell; Abel Escamilla; Wanxiang Yao; Tianou Zhang; Meizi He; John Q. Zhang (Elsevier, 2024)
Objective: The purpose of this study was to investigate the effects of different exercise intensities on postprandial lipemia (PHTG) and insulin resistance in healthy individuals. Methods: Participants were 10 adult males with normal fasting triglyceride (TG) concentrations (age = 34 ± 2.8 y, body mass = 72.9 ± 2.4 kg, fasting plasma TG = 1.36 ± 0.18 mmol/l, VO2max = 43.7 ± 3.0 ml/kg/min, fasting glucose = 5.2 ± 0.2 mmol/l and fasting Homeostatic Model Assessment for Insulin Resistance (HOMA2-IR) = 1.7 ± 0.3). In this study, each participant performed a control trial (Ctr, no exercise), and 3 exercise trials at 40 % (40%T), 60 % (60%T), and 70 % (70%T) of their VO2max. In the exercise trials, participant jogged on a treadmill for 1 h at a designated intensity. A fat-rich meal was consumed by each participant 12 h after exercise. Blood samples were taken at 0 h (before the meal), and 2 h, 4 h, 6 h, 8 h, and 24 h after the meal. The plasma TG, area score under TG concentration curve over an 8 h-period (TG tAUC) after the meal, and HOMA2-IR were analyzed. Results: Our results showed that at 2 h, 4 h, and 6 h after the meal, TG in all exercise trials were lower than Ctr (p < 0.05) but did not differ from each other. All the exercise trials were lower in TG tAUC scores than Ctr (p < 0.02), but differences were not observed among the exercise trials. In comparison to Ctr, a significant difference in HOMA2-IR in both 60 % T and 70 % T (p < 0.05 and p < 0.01, respectively) was observed, but not in 40 % T. Conclusion: The results suggest that exercising at low to moderate exercise intensity for 1 h sufficiently attenuates a fat meal induced PHTG. Moderate exercise intensity also effectively mitigates insulin resistance.